Solvent volume-driven CuInAlS2 nanoflake counter electrode for effective electrocatalytic tri-iodide reduction in dye-sensitized solar cells - Sudhagar Pitchaimuthu (Journal of Solid State Electrochemistry, 2018)
The influence of solvent volume on the properties of CuInAlS2 (CIAS) thin films deposited using simple and cost-effective nebulizer spray technique is studied. The polycrystalline CIAS thin films with tetragonal structure have been observed from the XRD results. SEM images show nanoflake-like structure on the film surface. The elemental presence and its chemical composition were examined by XPS and EDS. The deposited CIAS film for different solvent volume exhibited p-type semiconductor. Cyclic voltammetry, electrochemical impedance spectroscopy, and Tafel polarization measurements demonstrated that CIAS counter electrodes are capable of tri-iodide reduction process. The performances of photocurrent density-voltage for the CIAS CE exhibited the maximum efficiency of 2.55% with the short-circuit current density of 7.22 mA cm−2.